Efektivitas Bimbingan Kelompok Menggunakan Art Therapy dengan Teknik Menggambar untuk Mereduksi Perilaku Agresif - Rahmi Fratiwi; Zadrian Ardi; Nurfarhanah Nurfarhanah; Miftahul Fikri (Kuras Institute, 2026)
This study aimed to describe students' aggressive behavior and examine the effectiveness of group guidance services based on behavior modification using the Art Therapy drawing technique in reducing aggressive behavior. The study employed an experimental approach with a Single Subject Research (SSR) A–B design, involving eight junior high school students who met the research criteria. The participants exhibited aggressive behaviors, including both physical and verbal aggression, such as engaging in verbal conflicts, making threats, displaying hostility, mocking peers, hitting or pushing others, and damaging other people's belongings. Data were collected using a Likert-scale questionnaire to measure the level of aggressive behavior before and after the intervention. Data were analyzed using the Wilcoxon Signed-Rank Test and the N-Gain Test. The findings revealed a statistically significant difference between the pretest and posttest scores, with a significance value of 0.012 (p < 0.05), indicating that the intervention effectively reduced students' aggressive behavior. All participants showed a decrease in their aggression scores, demonstrating consistent behavioral improvement. Furthermore, the N-Gain result of 66% indicated that the intervention was moderately effective. The Art Therapy drawing technique proved to help students express their emotions constructively, improve self-control, and reduce aggressive tendencies. However, the intervention's effectiveness was not yet optimal due to internal and external factors affecting the participants. Therefore, strengthening the intervention through increased service intensity and greater environmental support is recommended to achieve more optimal and sustainable outcomes.